Life Insurance Premium Calculation Using Markov Chain for Hypertension Patients in Indonesia - Fenni Kurnia Mutiya; Marsika Sepyanda (Department of Mathematics, Universitas Negeri Padang (UNP), 2026)
Long-term care insurance provides death benefits if the insured dies and benefits for medical care costs during the coverage term. One of the products of this insurance is the Annuity Rider, as the Benefit can be modelled with a multi-state model. This paper discusses the calculation of annual premiums with Annuity riders as a Benefit product using a multi-state model for hypertension patients in Indonesia. The premium calculation also utilised Markov Chain transition probabilities. The data used in the Report Survey Kesehatan Indonesia in 2023. The case study was conducted on a 40-year-old male in good health, with LTC insurance coverage for 5 years. It was known that the compensation amount for someone who died was IDR 200,000,000, and the interest rate was 7%. By calculating premiums using the multi-state model, the results yielded an annual premium of IDR 6,486,998. The result of this premium calculation is that the older someone is when they take out insurance, the greater the annual net premium they must pay.